Obstetric profile of parturientes admitted in a Normal Birth Center in the region South Mato-Grossense (Research, Society and Development, 2022)
The Ministry of Health recognizes the need to propose improvements in care during childbirth and birth that are in line with the different needs of pregnant women. Thus, knowing the sociodemographic and obstetric profile enables the assessment of relevant factors for proper care. This study aimed to analyze the obstetric profile of parturient women admitted to an intra-hospital Normal Childbirth Center. This is a quantitative, cross-sectional study, carried out with data from a maternity hospital located in a large philanthropic hospital in a municipality in the south of Mato Grosso. The data refer to parturients attended from January to December of 2020, totaling 2,340 women. Variables related to age, obstetric history, number of prenatal consultations and others were analyzed. After analyzing the data, the results obtained were, by the majority of women aged between 19 and 35 years old, primigravid (38.4), with their usual risk births 1,266 (52.1%), assisted by nurses obstetrician 1,442 (59.4%), record 6 or more prenatal consultations (73.5%) and 89.2% of the parturients did not need to be referred for cesarean surgery.  It is concluded that the profile of parturients found corroborates the findings of national investigations and points to an obstetric service that meets the ministerial guidelines. The research findings will serve as feedback for the local health service, in addition to subsidizing the formulation of strategies for maternal and child care at regional and national levels, understanding the functioning of the obstetric care network and the relevance of the study to the scientific community.